Cosmological constraints on scalar field dark matter - Escobal, A. A. [UNESP]; Jesus, J. F. [UNESP]; Pereira, S. H. [UNESP] (World Scientific Publishing, 2021)
This paper aims to put constraints on the parameters of the Scalar Field Dark Matter (SFDM) model, when dark matter is described by a free real scalar field filling the whole universe, plus a cosmological constant term. By using a compilation of 51 H(z) data and 1048 Supernovae data from Panteon, a mass range for the scalar field was obtained, 7.8 × 10-35 ≤ m ≤ 10-17eV, in good agreement with light mass axion particles. Also, we have obtained H0 = 69.5-2.1+2.0 km s-1Mpc-1, and the present dark matter density parameter ωφ = 0.230-0.031+0.033 at 2σ confidence level. These results are in good agreement to standard model of cosmology, showing that SFDM model is viable in describing the dark matter content of the universe.
Keywords: Bayesian statistics; Cosmology; dark matter; scalar field